Effect of psychoeducation on coping strategies and anxiety levels of individuals with opiate use disorder - Uygun, Nesteren; Tarı Cömert, Itır (Journal of Dependence, 2025)
Objective: The purpose of this study is to examine the effects of psychoeducation applied to patients with opioid use disorder on their coping strategies and anxiety levels. Additionally, the study aims to investigate the relationship between coping strategies and anxiety levels.Method: The sample included 65 male patients aged 18–50, diagnosed with opioid use disorder, who were receiving treatment at the Alcohol and Substance Treatment Center (AMATEM) clinic of the University of Health Sciences Istanbul Erenköy Mental and Neurological Diseases Training and Research Hospital. Data were collected using a Demographic Information Form, the Coping Attitudes Scale, and the Beck Anxiety Scale.Results: After psychoeducation, participants showed a significant increase in overall coping attitudes, self-help, approach, and adaptation scores, while avoidance-escape, self-punishment, and anxiety scores significantly decreased. Conclusion: Psychoeducation provided on addiction at the treatment center for individuals with opioid use disorder was found to contribute positively to the development of coping strategies and the reduction of anxiety levels. It is suggested that such psychoeducation programs should be further developed and expanded.
Keywords: Opioid use disorder; psychoeducation; coping strategies; anxiety